Understanding bio-activity of salicylaldehyde related complexes - Yee, Alven Yi Long. (2010)
The structural optimizations of a series of salicylaldehyde semicarbazone (H2ssc)and their Cu(II) and Au(II) complexes of have been carried out using Density Functional Theory (DFT) calculations and their structural parameters comparatively analyzed. H2ssc and its complexes have been shown to exhibit tumour inhibitory activity with the metal complex of such ligands to display enhanced biological activities. Therefore a molecular understanding of metal-base therapeutic drugs has become of particular interest in bio-activity predictions for the purpose of drug design.